Mechanical ventilation enhances extrapulmonary sepsis-induced lung injury: role of WISP1–αvβ5 integrin pathway in TLR4-mediated inflammation and injury - Ding, Xibing; Tong, Yao; Jin, Shuqing; Chen, Zhixia; Li, Tunliang; Billiar, Timothy R.; Pitt, Bruce R.; Li, Quan; Zhang, Li-Ming (Critical care (London, England), 2018)
High tidal volume ventilation of healthy lungs or exacerbation of existing acute lung injury (ALI) by more moderate mechanical ventilation (MTV) produces ventilator-induced lung injury. It is less clear whether extrapulmonary sepsis sensitizes the lung to MTV. We used a two-hit model of cecal ligation and puncture (CLP) followed 12 h later by MTV (10 ml/kg; 6 h) to determine whether otherwise noninjurious MTV enhances CLP-induced ALI by contrasting wildtype and TLR4 mice with respect to: alveolar-capillary permeability, histopathology and intrapulmonary levels of WNT-inducible secreted protein 1 (WISP1) and integrin β5; plasma levels of cytokines and chemokines (TNF-α, IL-6, MIP-2, MCP-1) and intrapulmonary neutrophil infiltration; and other inflammatory signaling via intrapulmonary activation of JNK, p38 and ERK. A separate cohort of mice was pretreated with intratracheal neutralizing antibodies to WISP1, integrin β5 or IgG as control and the presented phenotyping repeated in a two-hit model; there were 10 mice per group in these first three experiments. Also, isolated peritoneal macrophages (PM) from wildtype and TLR4 , MyD88 and TRIF mice were used to identify a WISP1-TLR4-integrin β5 pathway; and the requisite role of integrin β5 in WISP1-induced cytokine and chemokine production in LPS-primed PM was examined by siRNA treatment. MTV, that in itself did not cause ALI, exacerbated increases in alveolar-capillary permeability, histopathologic scoring and indices of pulmonary inflammation in mice that previously underwent CLP; the effects of this two-hit model were abrogated in TLR4 mice. Attendant with these findings was a significant increase in intrapulmonary WISP1 and integrin β5 in the two-hit model. Anti-WISP1 or anti-integrin β5 antibodies partially inhibited the two-hit phenotype. In PM, activation of TLR4 led to an increase in integrin β5 expression that was MyD88 and NF-κB dependent. Recombinant WISP1 increased LPS-induced cytokine release in PM that was inhibited by silencing either TLR4 or integrin β5. These data show for the first time that otherwise noninjurious mechanical ventilation can exacerbate ALI due to extrapulmonary sepsis underscoring a potential interactive contribution of common events (sepsis and mechanical ventilation) in critical care, and that a WISP1-TLR4-integrin β5 pathway contributes to this phenomenon.